2009
DOI: 10.1021/ja807814x
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Intermolecular Interaction Inducing Pyramidalization on Both Sides of a Proline Dipeptide during Isomerization: An Ab Initio QM/MM Molecular Dynamics Simulation Study in Explicit Water

Abstract: The cis-trans isomerization of the peptide bond preceding a proline plays important roles in protein folding and biological function. Although many experimental and theoretical studies have been done, the mechanism has not yet been clearly elucidated. We studied the cis-trans isomerization of the proline dipeptide (Ace-Pro-NMe) in explicit water by molecular dynamics simulations using a combined potential derived from ab initio quantum mechanics and empirical molecular mechanics. We obtained the free energy la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 31 publications
8
33
0
Order By: Relevance
“…However, in the transition state, the geometry of the prolyl nitrogen changes from trigonal planar to tetrahedral-like, which moves the nitrogen out-of-plane, giving rise to a pyramidal structure. As was done by Yonezawa et al, 48 we defined the degree of pyramidality as the volume of the tetrahedron formed by four atoms: prolyl nitrogen, carbonyl carbon of the preceding residue, C R , and C δ . We generated a two-dimensional free-energy landscape along the ω dihedral and pyramidality (Figure 3).…”
Section: Testing the Transferability Of The Modified ω Torsional Paramentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the transition state, the geometry of the prolyl nitrogen changes from trigonal planar to tetrahedral-like, which moves the nitrogen out-of-plane, giving rise to a pyramidal structure. As was done by Yonezawa et al, 48 we defined the degree of pyramidality as the volume of the tetrahedron formed by four atoms: prolyl nitrogen, carbonyl carbon of the preceding residue, C R , and C δ . We generated a two-dimensional free-energy landscape along the ω dihedral and pyramidality (Figure 3).…”
Section: Testing the Transferability Of The Modified ω Torsional Paramentioning
confidence: 99%
“…This is consistent with previous ab initio quantum mechanical MD studies. 30,48 Conclusion Generally, AMBER parameters for dihedrals are derived from fitting to relative energies of various ground state conformations obtained from quantum mechanical calculations on model compounds. In some cases, dihedral parameters are based on experimental data from thermodynamic and kinetic studies on the rotation of a specific torsional angle.…”
Section: Testing the Transferability Of The Modified ω Torsional Paramentioning
confidence: 99%
“…It extended to 1.39 Å at 90°and 270°. The extension was clear evidence for the change in the character of the amide bond from an sp 2 to an sp 3 -hybridized electronic state, which reduces the rotational barrier of the isomerization to some extent [21]. It should be noted that the x dependence of the CAN bond length and that of the free energy landscape are well correlated.…”
Section: The Can Bond Lengthmentioning
confidence: 83%
“…doi:10.1016/j.cplett.2011.01.015 the system is sampled along an improper dihedral angle, C(@O)ANAHAC(AH3). Pyramidal conformations have been found both experimentally [16][17][18] and theoretically [19][20][21] to be associated with a lowered rotational barrier for the C(@O)AN bond. Even a small degree of pyramidal conformation has structural, spectroscopic, and chemical consequences.…”
Section: Introductionmentioning
confidence: 94%
“…The study of the poly-l-proline revealed that the cis isomer of proline is conformationally compact and that, conversely, the trans isomer appears more stable in solvents such as water and TFE (Schimmel and Flory 1967;Deber et al 1970;Andreotti 2003). Kinetic studies performed by NMR (Buevich et al 2000) directly indicated that proline isomerizes by a single-step mechanism with an energy of 14-24 kcal mol −1 (Stein 1993;Fischer 2000) and that the interconversion is considered the rate limiting step in the folding of protein (Schmid and Baldwin 1978;Fischer 2000;Wedemeyer et al 2002) with a defined transition state (Yonezawa et al 2009). …”
Section: Discussionmentioning
confidence: 99%